Cytopathology of larval tissues of Mamestra Brassicae L.(Lepidoptera, Noctuidae), infected with a nuclear polyhedrosis virus. - M., Vanhaecke (1988)
Virus-infected last instar larvae of Mamestra brassicae L. (Lepidoptera, Noctuidae) were collected from a laboratory culture. External symptoms such as white or pink discolouration of the integument, fracture of the cuticle and subsequent release of white body fluids from moribund larvae were indicative of nuclear polyhedrosis virus (NPV) infection. At the light microscope level occlusion bodies of the Mamestra brassicaeNPV were observed in the nuclei of the visceral fat body, the matrik cells of the tracheae and the epidermal cells. In the early stages of infection and virus replication, nuclei are enlarged and filled with virogenic stroma. Fat body cells lack the osmophilic fat droplets in their cytoplasm at this stage. Later occlusion bodies appear in the nucleoplasma and finally greatly enlarged nuclei, filled with polyhedra, occupy almost the entire cell volume. Nuclear and cell membranes burst and their contents together with the viral polyhedra mix with the haemolymph. At the electron microscope level, other pathological changes inside the nucleus are the infolding and concurrent reduplication of the inner nuclear membrane. In the cytoplasm of infected cells mitochondria are swollen and eventually are subjected to cristolysis. Tubuloreticular membrane structures are associated with them.